Evaluation of Compliance with a Weight-based Nurse-driven Heparin Nomogram in a Tertiary Academic Medical Center. Issue 2 (June 2018) - Schurr, James W.; Stevens, Craig A.; Bane, Anne; Culbreth, Sarah E.; Miller, Amy Leigh; Connors, Jean M.; Sylvester, Katelyn W.
Abstract : Background: Recently, our institution adopted a weight-based nurse-driven heparin titration protocol that relies on nurses ordering laboratories, adjusting doses, and initiating boluses. Numerous institutions have implemented similar protocols with reported success. Methods: A single-center retrospective analysis was conducted at the Brigham and Women's Hospital in Boston, Massachusetts that included all patients who were initiated on the weight-based nurse-driven heparin nomogram during a 30-day period. Nomogram compliance was defined as the rate of correct titrations per nomogram encounter and further separated into laboratory, titration, or dosing compliance. Spearman's coefficient was utilized to determine the correlation between noncompliance and percentage of activated partial thromboplastin time (aPTT) values in range. Results: Overall, 211 patients were evaluated for inclusion, of which 95 patients were determined to meet criteria for evaluation. The total nomogram compliance rate was 84.6% ± 10.5%. Laboratory, titration, and dosing compliances were 77.6% ± 19.2%, 87.2% ± 14.5%, and 91.8% ± 10.6%, respectively. The percent of aPTT values in therapeutic range was 39.6% ± 24.6%. A moderate negative correlation between the percentage of aPTT values in range and the nomogram error rate was observed ( r = −0.452, P < 0.001). This relationship was found to be driven by the rate of dosing error, which showed the strongest correlation with percentage of aPTT values out of range ( r = −0.465, P = 0.001). Conclusions: Implementation of a nurse-driven heparin titration nomogram relies on compliance with the prescribed protocol. Dosing compliance had the lowest error rate, whereas dosing noncompliance had the strongest impact on percentage of aPTT values in range.